Evaluation of Collagen Triple Helix Repeat Containing-1 protein in Postmenopausal Women with Osteoporosis - Isam Salman; Noor Ulhuda Mohammed; Rand Jalal Abd Al-Ghanny; Baydaa Abed; Samara mutar (مجله كليه طب الكندي)
Background: The collagen triple helix repeat containing 1 (CTHRC1) protein has been connected to decreased levels of vitamin D and calcium, as well as obesity. This study aimed to investigate the relationship between CTHRC1 and osteoporosis in post-menopausal women and compare with healthy subjects.